A new species and reconsiderations in Aeschynomene series Scopariae (Leguminosae, Papilionoideae) in Mexico - Rudd, Velva E. (Instituto de Ecología, A.C., 1989)
Aeschynomene lyonnetii sp. n., from the state of Guerrero, is described; in addition, two collections possibly representing new, undescribed species are noted; Ae. pringlei Rose, from the state of Morelos, is reinstated as a good species; Ae. ormocarpoides Rudd, in the state of Oaxaca, is recognized as a Diphysa; Ae. vigil Brandegee, from Baja California Sir, is better placed in series Pleuronerviae rather than in series Scopariae.